Development and Feasibility Evaluation of an MIT App Inventor-Based Android Interactive Learning Application for Basic Computer and Networking in a Vocational High School - Moh. Mazhud Hasyim; Firman Jaya; Rahmat Shofan Razaqi (Education Specialist, 2026)
Vocational learning in Basic Computer and Networking requires interactive media that can visualise technical concepts, guide practice, and support independent study. This study developed and evaluated an Android-based interactive learning application for the Basic Computer and Networking subject at State Vocational School 1 Kendit, Indonesia. A research-and-development approach was applied using the ADDIE model. The application was built with MIT App Inventor and included learning materials, instructional videos, practice questions, interactive evaluation, and usage guidance accessible through Android devices. Participants consisted of one material expert, one media expert, one subject teacher, and 25 Grade X Computer and Network Engineering students. Data were collected using observation, interviews, validation sheets, user-response questionnaires, and documentation. The product obtained a material-expert validation score of 94.0%, with content, presentation, and language all in the very valid category. Media validation reached 93.0%, indicating that the visual design, navigation, interactivity, and software-engineering aspects were highly feasible. Classroom implementation showed positive student and teacher responses, particularly regarding ease of use, visual appeal, and support for self-directed learning. The findings demonstrate that an MIT App Inventor-based Android application can serve as a feasible learning medium for vocational computer-networking instruction. The study contributes a context-sensitive development model for transforming students' smartphone familiarity into structured learning activity. Because effectiveness was not tested using a controlled experimental design, future studies should examine learning gains, retention, and long-term classroom integration.